Review of the efficacy and safety of over-the-counter medicine (Brazilian Journal of Pharmaceutical Sciences, 2015)
Over-the-counter medicines are available without prescription because of their safety and effectiveness, to treat minor ailments and symptoms. The objective of the study was to analyze the availability and quality of systematic reviews published about nonprescription medicines, identifying the groups for which there are gaps in evidence. We identified published articles through the Cochrane Database of Systematic Review and MEDLINE, from the start of the database until May 2012, using the search terms "nonprescription drugs," "over the counter," and "OTC." We searched for articles that describe systematic reviews addressing the efficacy and safety of drugs dispensed without a prescription, according to the lists published by the Association of the European Self-Medication Industry and in Brazil, in the clinical conditions listed in Groups and Specified Therapeutic Indications. We included 49 articles, 18 articles were of moderate quality and 31 of high quality. Of the studies, 74.5% demonstrated efficacy in favor of the use of drugs evaluated. Of the 24 studies that evaluated safety, 21% showed evidence unfavorable to the drug. Overall, the evidence found in the studies included in the overview is favorable to the use of the drugs evaluated. However, there are gaps in evidence for some therapy groups.